Fundamentals of entrepreneurship (ENT300) : Sam’s Centre Samarahan / Hashmaimah Abdullah … [et al.] - Abdullah, Hashmaimah; Mad Suliman, Mohd Azam; Appolonius, Norbert; Ismail, Nurul Izzah (2019)
Sam’s Centre is recognized and very famous among UiTM Samarahan students as well as UNIMAS students. This is due to the location of the company which is just behind the Seri Mulu College and it is also near for the students to come and visit the company branch. Moreover, the company also offering the main needs for the students such as printing services and stationery. The Sam’s Centre perceive to have miscellaneous benefits. The printing quality just as expected and meet customer’s need.